1997
DOI: 10.1542/peds.100.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Multiple Doses of Recombinant Human CuZn Superoxide Dismutase Administered Intratracheally to Premature Neonates With Respiratory Distress Syndrome

Abstract: These data indicate that multiple IT doses of rhSOD increase the concentration and activity of the enzyme in serum, TA and urine, reduce TA lung injury markers and are well-tolerated. Further clinical trials examining the efficacy of rhSOD in the prevention of BPD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 18 publications
1
64
0
1
Order By: Relevance
“…doses of rhSOD given to premature infants (700 to 1300 gm) with RDS resulted in significant increases in SOD concentration and activity in serum, tracheal aspirates, and urine. 8,9 A variety of cell and biochemical markers of inflammation in tracheal aspirates that appear to be associated with the development of BPD were significantly reduced in rhSOD-treated infants compared with placebo controls. The drug appeared to be well tolerated in the dosage ranges used (0.5 to 5.0 mg/kg) and not associated with any demonstrable short-term abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…doses of rhSOD given to premature infants (700 to 1300 gm) with RDS resulted in significant increases in SOD concentration and activity in serum, tracheal aspirates, and urine. 8,9 A variety of cell and biochemical markers of inflammation in tracheal aspirates that appear to be associated with the development of BPD were significantly reduced in rhSOD-treated infants compared with placebo controls. The drug appeared to be well tolerated in the dosage ranges used (0.5 to 5.0 mg/kg) and not associated with any demonstrable short-term abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…doses of rhSOD. 8,9 These studies have established the short-term safety of rhSOD and have suggested that early inflammatory changes in the lung, which appear to be associated with the development of BPD, can be significantly reduced. The current study prospectively examines the longer-term neurodevelopmental and pulmonary outcomes of infants who received i.t.…”
mentioning
confidence: 99%
“…In a small study, the intratracheal application of recombinant human SOD (rhSOD) in two different dosages every 48 hours up to seven doses was well tolerated by VLBW infants and led to an increased SOD concentration in tracheal aspirate fluid and serum. 44 Neutrophil chemotactic activity was significantly reduced in tracheal aspirate samples of the two intervention groups but the trial failed to show any beneficial effect of the study drug on BPD at 28 days of life or 36 weeks postmenstrual age. In a recently published larger multicenter trial, 302 infants with birth weights of 600 to 1200 grams who were mechanically ventilated and treated with surfactant for respiratory distress syndrome were randomized to receive either intratracheal rhSOD or placebo every 48 hour up to 1 month.…”
Section: Methylxanthinesmentioning
confidence: 93%
“…Markers of lung injury in the tracheal aspirate were lower in the treated infants [44]. Subsequently, in a multicentre randomised control trial (RCT), 302 infants were treated with either intra-tracheal rhCuZnSOD or placebo every 48 hours while they remained mechanically ventilated until a postnatal age of 28 days.…”
Section: Superoxide Dismutase Replacementmentioning
confidence: 99%